Optimization of 2,3-Butanediol Production by Klebsiella pneumoniae PTCC 1290 Using Taguchi Methodology - Anvari, Masumeh; Khayati, Gholam (Asian Journal of Chemistry, 2010)
2,3-Butanediol production parameter optimization using Klebsiella pneumoniae PTCC 1290 was performed using the design of experiments available in the form of an orthogonal array and a software for automatic design and analysis of the experiments, both based on Taguchi protocol. Optimal levels of physical parameters and key media components namely temperature, pH, inoculum size, agitation, acetic acid and succinic acid were determined. 2,3-Butanediol production obtained from the 18 sets of fermentation experiments performed with the selected factors and levels were further processed with Qualitek-4 software at bigger is better as quality character. The optimized conditions showed an enhanced 2,3-butanediol production of 35.8 % (from 11.856 to 18.459 g L-1). The optimal combinations of factors obtained from the proposed design of experiments methodology was further validated by conducting fermentation experiments and the obtained results revealed an enhanced 2,3-butanediol production of 25.8 %. Taguchi approach of design of experiments resulted in evaluating the main and interaction effects of the factors individually and in combination. This methodology facilitated analysis of the experimental data to establish the optimum conditions for the process, understand the contribution of individual factors and to evaluate the response under optimal conditions.